2019
DOI: 10.1371/journal.pone.0220185
|View full text |Cite
|
Sign up to set email alerts
|

Role of carbonic anhydrase in acute recovery following renal ischemia reperfusion injury

Abstract: Ischemia reperfusion (IR) injury can cause acute kidney injury. It has previously been reported that kidney oxygen consumption (QO 2 ) in relation to glomerular filtration rate (GFR), and thus tubular sodium load, is markedly increased following IR injury, indicating reduced electrolyte transport efficiency. Since proximal tubular sodium reabsorption (TNa) is a major contributor to overall kidney QO 2 , we investigated whether inhibition of proximal tubular sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Importantly, in addition to urine alkalization, we used TRPC3 KO mice in this study because these mice are moderately hypercalciuric [ 18 ], a condition which is conducive for CaP stone formation. Acz was recently used in experimental models for ischemic reperfusion injury recovery, however its CA inhibition further impairs renal oxygenation [ 45 ]. Moreover, Acz has also been proposed as a treatment adjunct for patients with cystine and uric acid stone formation to standard alkalization therapy [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, in addition to urine alkalization, we used TRPC3 KO mice in this study because these mice are moderately hypercalciuric [ 18 ], a condition which is conducive for CaP stone formation. Acz was recently used in experimental models for ischemic reperfusion injury recovery, however its CA inhibition further impairs renal oxygenation [ 45 ]. Moreover, Acz has also been proposed as a treatment adjunct for patients with cystine and uric acid stone formation to standard alkalization therapy [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The observed differences in K + clearance particularly for the treated groups provide explanation for the observed increase in urinary pH among the treated groups. Studies have shown that, Acz results in increased Na + clearance which can be as a result of Acz’s inhibitory action on CA [ 45 , 52 ]. Similarly, Na + excretion is directly related to decrease in K + excretion which is associated with increasing serum K + levels [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rats were kept under general anesthesia throughout the experiment. Under this condition, they found that acetazolamide impaired renal oxygenation, increased oxygen consumption, and decreased GFR compared to vehicle-treated rats [108]. In small human trials, there is some evidence to suggest that acetazolamide ameliorates contrast-, cisplatin-, cardiopulmonary bypass-and rhabdomyolysis-induced AKI (Table 1) [62][63][64]109,110].…”
Section: Acetazolamidementioning
confidence: 97%
“…They found that acetazolamide reduced AKI by restoring renal blood flow, an effect that was associated with in-creased endothelial nitric oxide synthase (eNOS) activity, nitric oxide (NO) production, hypoxia inducible factor 1 subunit alpha (HIF-1α) expression, and decreased vascular permeability [107]. Conversely, Nensen et al [108] intravenously injected 50 mg/kg of acetazolamide into rats 45 minutes prior to clamping the renal pedicle for 45 minutes unilaterally and then allowed reperfusion for 2 hours. Rats were kept under general anesthesia throughout the experiment.…”
Section: Acetazolamidementioning
confidence: 99%